مساهمة في دراسة خصوبة السرطان الأزرق Portunus pelagicus (Linnaeus,1758) وبعض صفاته الحيوية في شاطئ اللاذقية (Latakia University Journal -Biological Sciences Series, 2013)
تناول هذا البحث لأول مرة دراسة الخصوبة عند النوع Portunus pelagicus السرطان الأزرق في مياهنا الإقليمية كمقدمة لتربيته واستزراعه. نفذت هذه الدراسة في الفترة الممتدة من أيلول 2011 حتى كانون الثاني 2013 , في المناطق الثلاث التالية من شاطئ اللاذقية: منطقة ابن هانئ, منطقة مرفأ الصيد والنزهة ومنطقة الكورنيش الجنوبي. جمعت العينات بمعدل مرتين شهرياً من المنطقة الشاطئية Littoral والمنطقة تحت الشاطئية Sublittoral ومن عمق 8-18 m . بلغ عدد الإناث الناضجة 240 أنثى تراوح عرض درقاتها 5.2-13, 8 cm وطول درقاتها4.6-7.9cm وأوزان أجسامها 49.2-171.45 g . أظهرت نتائج هذه الدراسة ما يأتي: تحدث الإباضة خلال الفترة الممتدة من أيار حتى كانون الأول وبمعدل أعلى في شهر تشرين الأول. تراوحت الخصوبة المطلقة عند الإناث بين 21435-143510 بيضة, والخصوبة النسبية بين 1924-766651 بيضة/غ , وتراوحت أقطار البيوض 0.25-0.45mm . This research deels for the first time the studying fecundity of species blue crab Portunus pelagicus in our regional waters which as an introduction to breeding and culture. This research carried out in the period from September 2011 until January 2013. At the following three region of Lattakia coast : Fishing bort and picnic area, Ibn Hanni area and Southern Corniche area.Biomonthly samples were collected from Littoral and Sublittoral area of 8-18m deeps. Studies results revealed as the following: The number of mature females 240 female, Ranged: carapace length 4.6-7.9cm Carapace width between 5.2-13.8cm and body weight between 49.2-171.45 g . Spawning takes plase during the period from May until December and the rate of the highest in the month of October. Absolute fecundity in females of this species was ranged between 21435-143510 eggs, and relative fecundity was ranged between 1924-766651 eggs/g, and the eggs diameters ranged between 0.25-0.45 mm.